Effects of Fluid Modernity on the Language Culture of Professional Communication - Zbróg, Piotr (Respectus Philologicus, 2014)
This article presents the results of research into the language culture of professional communication given the fluid nature of modern communication. The scope of interest is direct linguistic relations between professional senders and recipients of texts. As in the general culture, in professional communication the paradigms which have been used until now (in which the observance of specific stylistic and correctness indicators is recommended) are being dropped. As such, many senders make use of different styles and varieties of utterance at the same time, combining them freely within one text (e.g., formal and informal, careful and colloquial, etc.). Colloquial lexis (e.g., ogarnij się, ruchy, pierdoły) and linguistic forms which are incorrect according to the contemporary norm (e.g., na wiosce, mi się to podoba) are being added to customarily careful utterances—sermons, news reports, and lectures at school and university. Using the language in a temporary way, without any limitations and rigid confines, is becoming the rule. Senders use this way of speaking both to gain acceptance and to surprise recipients with unusual stylistic and lexical combinations. These new linguistic customs are especially visible among the most skillful language users, those who have a broad stylistic workshop and a large store of rhetorical devices. They appears not to fear shaking up the language system in connection to the observed changes. In the fluid modernity there is a self-restraining mechanism: one’s responsibility to make every utterance comprehensible to the recipient. Professional communication would otherwise be impossible.